2011
DOI: 10.1166/jnn.2011.4169
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bioconjugated Quantum Dots Passivated with Different Ligands for Bio-Applications

Abstract: Bioconjugation of quantum dots has resulted in a significant increase in resolution of biological fluorescent labeling. This intrinsic property of quantum dots can be utilized for sensitive detection of target analytes with high sensitivity; including pathogenic bacteria and cancer monitoring. The quantum dots and quantum dot doped silica nanoparticles exhibit prominent emission peaks when excited at 400 nm but on conjugation to model rabbit antigoat antibodies exhibit diminished intensity of emission peak at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…GQDs-biosurfactant conjugates (biosurfactant-GQDs) were separated from free cross-linkers by centrifugation (6,000 rpm, 5 minutes) and kept at 4°C. 1,23…”
Section: Preparation Of Gqds-biosurfactant Conjugatesmentioning
confidence: 99%
See 3 more Smart Citations
“…GQDs-biosurfactant conjugates (biosurfactant-GQDs) were separated from free cross-linkers by centrifugation (6,000 rpm, 5 minutes) and kept at 4°C. 1,23…”
Section: Preparation Of Gqds-biosurfactant Conjugatesmentioning
confidence: 99%
“…Finally, purified folate conjugated GQDs (FA-biosurfactant-GQDs) were stored at 4°C till further use. 1,23,32 characterization GQDs and their bioconjugates were characterized by spectrophotometeric techniques such as transmission electron microscopy (TEM), Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and zeta potential. The optical studies were investigated by PL and UV-visible spectroscopy.…”
Section: Preparation Of Gqds-biosurfactant-fa Conjugatementioning
confidence: 99%
See 2 more Smart Citations
“…These functional QD probes have been increasingly used in cellular and molecular tracing, in vivo tumor imaging, drug monitoring, and signal transduction. [3][4][5][6][7][8] Since the core components of QDs are heavy metals (such as Cd, Se, and so on), their toxicity and biosafety have aroused general concern. 9,10 Some studies have shown that due to the release of heavy metals from the QD core and the generation of reactive oxygen free radicals induced by QDs in cells, QDs are toxic to the organism and cells.…”
Section: Introductionmentioning
confidence: 99%